Pengaruh Zat Pengatur Tumbuh (ZPT) Terhadap Pertumbuhan Stek Kayu Putih (Melaleuca leucadendron Linn) - farihah fitsa qoni; Mahayu Woro Lestari; Indiyah Murwani (AGRONISMA, 2022)
Eucalyptus (Melalauca leucadendron Linn) is one of the essential oil-producing plants. Eucalyptus in Java Island has a factory capacity of 53,760 tons per year so that this plant has great potential to be developed. Propagation of plants by seed takes a long time, so efforts are needed to develop more effective vegetative propagation techniques for the development of plantation forests. One of the cultivation techniques that can be pursued is shoot cuttings, which is a vegetative plant propagation technique that has better genetic advantages than the parent. PGR contains the hormone auxin which functions on plant root growth so that it greatly affects the success of eucalyptus shoot cuttings. This study aims to determine the best growth on eucalyptus shoot cuttings using a variety of Growth Regulatory Substances (ZPT) Rootone – F onion extract and young coconut water. with the right concentration. This research was conducted in the Jatirejo Nursery belonging to the East Java Regional Division of Perum Perhutani KPH Kediri City with an altitude of 221 masl, temperature ± 30°C, humidity 70% to 80% and rainfall averaged 1500mm per year. The experimental design used was a factorial randomized block design (RAK) consisting of 2 factors, namely factor 1 was the type of PGR (Z1 = Rootone – F, Z2 = Shallot Extract and Z3 = Young Coconut Water) and factor 2 was the concentration of the solution (K1 = 50% solution concentration, K2 = 75% solution concentration and K3 = 100% solution concentration). From the two factors, 9 treatment combinations were obtained plus 1 treatment, namely control (without PGR). Observational data were analyzed using the F test with a further test of BNT and Dunnet as a control comparison at the 5% level. The results showed that the growth of shoots on eucalyptus shoot cuttings with the application of different types of PGR did not show a significant difference in the growth of the number of shoots and the number of leaves. The right PGR for optimum growth on eucalyptus shoot cuttings is by using natural PGR of coconut water with a concentration of 100% and onion extract with a concentration of 75%, while for the use of synthetic PGR, Rootone - F with a concentration of 50%.                  Key words : Eucalyptus, Growth Regulatory Substance (ZPT), Shoot Cuttings